Pengaruh Media Buku Berjendela terhadap Kemampuan Literasi Sains Peserta Didik Kelas V UPT SDN 064964 Medan Timur - Amini, Fatimah; Wulandari, Fadilah; Rizky, Seri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research was conducted because the researchers observed that students couldn't understand the process of food digestion in the human body, and they also lacked an understanding of the human digestive organs. The aim of this study was to improve students' learning outcomes on the topic of human digestive organs by using a windowed book media so that students could better understand how the process of food digestion occurs from the mouth to the esophagus. This research used a quantitative approach and various research methods, one of which was the experimental method. The experimental method can create problem-solving experiments that can make students think critically and develop scientific literacy. The results of this research show that the windowed book media on the topic of the Function of Human Digestive Organs and its Relationship with Food and Health met the criteria for validity and practicality, with an average score of 80% for language validation, which can be considered good, an average expert media validation score of 83%, or very good, and for the posttest score, the average score was 88.3, compared to the pretest score of 31.25. Therefore, the windowed book media has met the criteria for validity and can be used by teachers. Based on the research findings, the following recommendations can be made: 1) For teachers, the delivery of learning materials should be accompanied by the use of interesting media, namely the use of windowed book learning media. 2) For schools, they can encourage teachers to be more creative in creating or providing suitable learning media that support the learning process. One alternative learning media that can be used is the windowed book learning media. 3) For researchers, realizing the imperfection of this research and the development of the windowed book media, further research and development should be conducted in the future to improve this research and create a new product in the field of research and development in science subjects as well as other subjects.